AICAR Attenuates TNFα-Induced Inappropriate Secretion of Monocyte Chemoattractant Protein-1 and Adiponectin in 3T3-L1 Adipocytes - Nagahara, Keiko (J Atheroscler Thromb, 2016)
Aim: The increase in monocyte chemoattractant protein-1 (MCP-1) and the decrease in adiponectin production from hypertrophic adipocytes are associated with adipose tissue inflammation and its metabolic complications. The aim of this study was to determine whether 5-aminoimidazole-4-carboxamide 1-β-D-ribofuranoside (AICAR), an adenosine monophosphate-activated protein kinase (AMPK) activator, modulates these adipocytokine productions in tumor necrosis factor-α (TNFα)-treated adipocytes. Methods: AICAR and/or other reagents were added to the culture medium, and then, TNFα was added to fully differentiated 3T3-L1 adipocytes. The MCP-1 and adiponectin production in the culture supernatant was measured by ELISA. AMPK, phosphatidylinositol 3-kinase (PI3K), and nuclear factor-κB (NF-κB) activities were also assayed. Results: Treatment with TNFα increased MCP-1 and decreased adiponectin secretion dose-dependently in the 3T3-L1 adipocytes, and AICAR significantly inhibited these TNFα-mediated changes. Interestingly, metformin, another AMPK activator, did not have such effects on these adipocytokines. Both the AMPK and PI3K systems in the cells were significantly activated by the AICAR treatment, but the effects of AICAR on adipocytokines were not weakened by the addition of dorsomorphin, an AMPK inhibitor, or LY294002, a PI3K inhibitor. Pyrrolidine dithiocarbamate (PDTC), an NF-κB inhibitor, showed protective effects similar to those as AICAR. AICAR, but not metformin, significantly inhibited the TNFα-stimulated activation of NF-κB, and dorsomorphin did not change AICAR's effect. Conclusion: AICAR attenuates the TNFα-induced secretion of MCP-1 and adiponectin in 3T3-L1 adipocytes. The observed effects of AICAR seem to be mainly due to the inhibition of NF-κB activation rather than the activation of the AMPK pathway, at least in TNFα-treated adipocytes.